Is the idyl the story we were told? The vision of future teachers about seduction and courtship - De la Mata Agudo, Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The study explores how a group college students perceive the seduction and courtship. This study is part of an investigation in which future teachers were asked about decisive films that they would work on in the classroom. The films showed sexist stereotypes and myths of romantic love. The study explores whether the speeches with which the seduction is narrated share the representations of romantic love.